2020
DOI: 10.1186/s12889-020-8440-3
|View full text |Cite
|
Sign up to set email alerts
|

High risk men who have sex with men in Spain are reporting low intentions of actively seeking HIV testing: results from a cross-sectional study

Abstract: Background: We analyse unprotected anal intercourses (UAI) self-reported by a sample of men who have sex with men (MSM), by their future testing intentions and past testing history to identify undertested subpopulations that could be contributing to onward transmission. Methods: We recruited MSM through gay dating websites in Spain from September 2012 to April 2013. For MSM at risk of acquiring or unknowingly transmitting HIV (at risk hereafter) we calculate time at risk, number of UAI in the last 12 months an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…On the other hand, among MSM who had a previous HIV negative test, those who reported condomless receptive anal sex were more likely to accept an HIVST. A study conducted in Spain showed that MSM reporting high-risk behaviors had greater intentions to test [56].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, among MSM who had a previous HIV negative test, those who reported condomless receptive anal sex were more likely to accept an HIVST. A study conducted in Spain showed that MSM reporting high-risk behaviors had greater intentions to test [56].…”
Section: Discussionmentioning
confidence: 99%
“…On the other rand, among MSM who had taken an HIV, those who reported a recent condomless receptive anal sex were much likely to accept HIVST. A study conducted in Spain documented that MSM with high-risk infection behaviors had high intentions to do a future HIV testing [44]. Furthermore, this phenomenon in our research may be due to the high-risk perception found among this subgroup (data not showed).…”
Section: Discussionmentioning
confidence: 51%
“…Six studies suggested a previous negative experience of the testing process to be an important barrier to HIV/STI testing [ 28 , 31 , 32 , 33 , 34 , 35 ]. Common themes which emerged included feeling embarrassed during previous testing experiences and discomfort about discussing their sexual history.…”
Section: Resultsmentioning
confidence: 99%
“…Tester characteristics was an important consideration, particularly tester credibility/legitimacy [ 18 , 28 , 32 , 35 , 49 ], attitude [ 28 , 32 , 33 , 42 , 71 , 72 ], skill/knowledge [ 18 , 32 , 34 , 37 , 71 , 72 ] and familiarity with tester [ 18 , 28 , 29 , 36 ]. Gender of tester was not identified as an important consideration in any studies.…”
Section: Resultsmentioning
confidence: 99%